HUBUNGAN KESEMBUHAN PASIEN TUBERKULOSIS PARU DENGAN ADA TIDAKNYA PENGAWAS MENELAN OBAT (PMO) DI RUMAH SAKIT ATMA JAYA - Fariz Abdul Mujib Dailami; Regina Satya Wiraharja; Febie Chriestya Chriestya (Bahasa Indonesia, 2019)
Introduction: One of the biggest health problems faced by community is pulmonary tuberculosis (TB).TB is an respiratory tract infectious disease caused by Mycobacterium Tuberculosis. World Health Organization (WHO) recommends TB treatment with Directly Observed Treatment Short-course (DOTS) strategy, one of which is through the help of treatment supporter (PMO or Pengawas Minum Obat) who supervises the patient during the treatment period. Methods: This was an analytic descriptive study with cross sectional approach.. Respondents were taken by consecutive sampling, based on medical records at Atma Jaya Hospital. We applied inclusion criteria such as newly diagnosed TB patient with positive sputum smear microscopy results, adult TB patient who has finished 6 month of treatment and patients who have done sputum smear microscopy test after finishing their TB treatment. The exclusion criteria were TB-HIV patients and Milliary TB patients. After fulfilment of those criteria, a total of 81 respondents were selected. Data was analysed by Chi Square test (Fisher Exact test). Results: Most of patients were 15-50 years old (70,4%) with mean age at 38.49±17.83 years old),male (53.1%), had family as treatment supporter (91.4%) and had successful TB treatment (74.1%). TB patients with treatment supporter had more successful treatment (66.7%) than TB patients with no treatment supporter (7.4%), however there was no significant among the avalibility of treatment supporter and the success of TB treatment (p=0.670). Conclusion: Despite the insignificant result, this study gives good insight to implementation of TB DOTS strategy in Atma Jaya Hospital. The implementation of this strategy contributes to imbalance number of samples between patient with and without treatment supporter, leading to overestimate results on with TB treatment supporter group.